Characterization of Some Portland Limestone Cements in Nigeria Using Fourier-Transform Infrared Spectroscopy (FTIR) - Danchuwa, Ibrahim Mohammed; Abatcha, Mustapha Zannah; Aliyu, Yazid; Yawale, Mohammed Buba; Abubakar, Walid Haruna; Umar Abubakar, Abdulhameed (Journal of Structural Monitoring and Built Environment, 2022)
In Nigeria, the most widely used cement strength class are 32.5 and 42.5 Portland limestone cement. However, due to lack of awareness, scientists and researchers are reporting the use of PLC as Ordinary Portland Cement (OPC). The study presents the characterization of PLC using absorption spectroscopy as well as oxide composition. Ratio between 7 - and 28 - day strengths of some selected PLCs are presented. It is seen that the Brands investigated conforms to the specifications of Portland composite cements in compliance with ASTM C150 and NIS 444-1. Absorption spectrum for the two brands were similar to that of OPC and exhibited similar characteristics. Concrete strength was within the designed concrete specification, and the ration between the two curing ages is 0.6 for both brands.